Therapeutic Touch Has Significant Effects on Mouse Breast Cancer Metastasis and Immune Responses but Not Primary Tumor Size. (31st May 2015) - Gronowicz, Gloria; Secor, Eric R.; Flynn, John R.; Jellison, Evan R.; Kuhn, Liisa T.
Abstract : Evidence-based integrative medicine therapies have been introduced to promote wellness and offset side-effects from cancer treatment. Energy medicine is an integrative medicine technique using the human biofield to promote well-being. The biofield therapy chosen for study was Therapeutic Touch (TT). Breast cancer tumors were initiated in mice by injection of metastatic 66cl4 mammary carcinoma cells. The control group received only vehicle. TT or mock treatments were performed twice a week for 10 minutes. Two experienced TT practitioners alternated treatments. At 26 days, metastasis to popliteal lymph nodes was determined by clonogenic assay. Changes in immune function were measured by analysis of serum cytokines and by fluorescent activated cells sorting (FACS) of immune cells from the spleen and lymph nodes. No significant differences were found in body weight gain or tumor size. Metastasis was significantly reduced in the TT-treated mice compared to mock-treated mice. Cancer significantly elevated eleven cytokines. TT significantly reduced IL-1-a, MIG, IL-1b, and MIP-2 to control/vehicle levels. FACS demonstrated that TT significantly reduced specific splenic lymphocyte subsets and macrophages were significantly elevated with cancer. Human biofield therapy had no significant effect on primary tumor but produced significant effects on metastasis and immune responses in a mouse breast cancer model.